What are The Optimal Surgical Staging Procedures for Fallopian Tube Cancer in Terms of Diagnostic Accuracy, Morbidity, and Long-Term Patient Outcomes? : A Systematic Review - Melati Ganeza (International Medical Journal Corp. Ltd, 2026)
Introduction: Primary fallopian tube cancer (PFTC) is a rare gynecologic malignancy that shares clinical and histological features with epithelial ovarian cancer. The optimal surgical staging procedures for PFTC and its precursor, serous tubal intraepithelial carcinoma (STIC), remain incompletely defined due to limited prospective data. Methods: This systematic review synthesized evidence from 16 studies, including RCT, etc. Data were extracted on diagnostic accuracy (upstaging rates), surgical morbidity, long-term outcomes (survival, recurrence), and comparative effectiveness of staging approaches (laparoscopy vs. laparotomy, complete vs. incomplete staging, extraperitoneal vs. transperitoneal lymphadenectomy). Results: For PFTC, comprehensive surgical staging (hysterectomy, bilateral salpingo-oophorectomy, omentectomy, lymphadenectomy, peritoneal cytology/biopsies) improved 5-year survival from 33.3% to 65.4% (p=0.043) (Yu et al., 2007). Optimal cytoreduction significantly improved survival (68.4% vs. 41.7%, p=0.044) (Yu et al., 2007). Upstaging rates for apparent early-stage adnexal cancers were 23% (Brockbank et al., 2013). For STIC, upstaging varied from 0% in BRCA carriers undergoing risk-reducing surgery (Hoeven et al., 2018) to 43% in incidental STIC in low-risk women (Chay et al., 2015). Minimally invasive staging reduced blood loss, hospital stay, and lymphatic ascites (p<0.05) compared to laparotomy (Nezhat et al., 2010; Pérez-Medina et al., 2015; Kerbage et al., 2020). Extraperitoneal para-aortic lymphadenectomy had fewer intraoperative complications (OR 0.40, p=0.001) but more lymphoceles (OR 4.12) than transperitoneal approach (Li et al., 2021). Discussion: The evidence supports complete surgical staging and optimal cytoreduction for PFTC. For STIC, staging is most clearly indicated when incidentally found in non-BRCA patients. Minimally invasive approaches are preferred due to lower morbidity, provided tumor rupture is avoided. The independent prognostic value of lymphadenectomy remains debated, while omentectomy shows consistent survival benefit. Conclusion: Optimal surgical staging for fallopian tube cancer should include systematic lymphadenectomy, omentectomy, peritoneal biopsies, and cytology, aiming for no residual disease. Laparoscopic staging is safe and effective for early-stage and selected advanced cases. STIC management should be individualized based on BRCA status and clinical context.